Rapid repairing material for tapping hole and furnace lining of intermediate frequency furnace
Patent Information
- Application Number
- CN202511158359.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-14
AI Technical Summary
Existing medium-frequency furnace lining and tap hole repair materials are difficult to form a high-strength, dense sintered layer quickly at high temperatures, and the bonding strength with the old lining is insufficient. This leads to problems with the strength, density, and material compatibility of the repair layer, which cannot meet the stringent requirements of the tap hole and results in a short repair life.
A rapid repair material composed of a specific ratio of tabular corundum, fused magnesia, alumina micro powder, nano-zirconia, silicon carbide, and silica sol is used. Calcium aluminate titanate coated with chromium nickel boride is added as a reinforcing agent. The material is then processed into strips using a vacuum extrusion machine to form a high-strength, dense sintered layer, enhancing its thermal shock resistance and corrosion resistance.
It forms sufficient strength at medium and low temperatures and rapidly forms a high-strength, dense sintered layer at high temperatures, significantly improving the high-temperature strength, toughness, and thermal shock resistance of the repair material, extending the repair life, and enhancing its erosion resistance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of furnace lining materials, specifically to a rapid repair material for the tap hole and furnace lining of a medium-frequency furnace. Background Technology
[0002] Medium-frequency induction furnaces, or simply medium-frequency furnaces, are widely used in casting and special steel smelting due to their advantages such as high heating efficiency, fast melting speed, flexible operation, and relatively good environmental performance. As a key component of the medium-frequency furnace, the furnace lining directly withstands the erosion, scouring, thermal shock, and chemical effects of high-temperature molten metal (such as molten steel and iron), as well as the slag's chemical action. The tapping area, in particular, is one of the weakest and most vulnerable parts of the lining due to the concentrated scouring of molten steel, rapid heating and cooling (the steel is exposed to air and cooled rapidly during tapping, then baked by the high-temperature furnace after flowing out), and slag erosion. Other areas of the furnace body, such as the slag line and molten pool wall, may also develop localized cracks, spalling, or erosion pits during use due to various reasons.
[0003] Damage to the furnace lining (especially at the taphole) directly affects the safe operation of the furnace, production efficiency, steel quality, and smelting costs. Severe damage can lead to furnace burnout accidents, causing significant economic losses and safety risks. Traditional solutions involve partial repairs or complete replacement of the furnace lining. Complete lining replacement is costly and requires a lengthy process of cooling, dismantling, relining, and drying the furnace, severely impacting production continuity.
[0004] Therefore, localized repair has become a key technology for extending furnace lining life and reducing operating costs. Existing technologies for repairing the lining and taphole of medium-frequency furnaces suffer from the drawback of difficulty in hot sintering. The sprayed material and hot repair paste struggle to quickly form a high-strength, dense sintered layer, and their bonding strength with the old lining is insufficient. Furthermore, issues with the strength, density, and material compatibility of the repair layer result in weak resistance to molten steel erosion and slag attack, leading to a short repair life, and particularly failing to meet the stringent requirements of the taphole. Summary of the Invention
[0005] In view of the problems existing in the prior art, the purpose of this invention is to provide a rapid repair material for the tap hole and furnace lining of an intermediate frequency furnace.
[0006] The objective of this invention is achieved through the following technical solution: In a first aspect, the present invention provides a rapid repair material for the taphole and lining of an intermediate frequency furnace, comprising, by weight parts: 50-70 parts tabular corundum, 10-20 parts fused magnesia, 8-15 parts alumina micro powder, 3-8 parts nano-zirconia, 5-12 parts silicon carbide, 10-15 parts silica sol and 2-5 parts reinforcing agent.
[0007] Preferably, the particle size distribution of the tabular alumina includes: 20%-40% by weight of particles with a diameter of 1-3 mm, 30%-50% by weight of particles with a diameter of 0.5-1 mm, and 20%-40% by weight of particles with a diameter less than 0.5 mm; the composition of the tabular alumina includes Al2O3≥99%, Na2O≤0.4%, and SiO2≤0.15%.
[0008] Preferably, the composition of the fused magnesia includes: MgO≥97%, SiO2≤1.2%, CaO≤1.5%, and the particle size of the fused magnesia is 0.088-0.5mm.
[0009] Preferably, the alumina micro powder has a purity of over 99.5% and a particle size of 0.8-1.2 μm.
[0010] Preferably, the purity of the nano-zirconia is higher than 99%, and the particle size is 20-50 nm.
[0011] Preferably, the particle size distribution of the silicon carbide includes: 50%-70% by weight of particles with a diameter of 0.5-1 mm, and 30%-50% by weight of particles with a diameter less than 0.5 mm.
[0012] Preferably, the mass percentage of SiO2 in the silica sol is 20%-55%.
[0013] Preferably, the reinforcing agent is calcium aluminate titanate coated with chromium nickel boride, with a particle size of 0.5-2 μm.
[0014] Preferably, the method for preparing the boronized nickel-chromium titanate coated calcium aluminate includes: S1. Weigh chromium nitrate, nickel nitrate and boric acid and add them to anhydrous ethanol. Add 2-3 drops of nitric acid, then add dispersant and stir thoroughly to obtain the precursor solution. S2. Weigh the calcium aluminate titanium dioxide powder, sonicate it in hydrochloric acid solution for 10-20 minutes, wash it with water and dry it to obtain pretreated calcium aluminate titanium dioxide powder. S3. Immerse the pretreated calcium titanate powder in the precursor solution, ultrasonically disperse for 20-40 minutes, heat to 70-80℃, keep warm and continuously stir to evaporate more than 90% of the solvent, and place in a drying oven at 200-300℃ for 1-3 hours to form the precursor-coated powder. S4. Place the precursor-coated powder in a tube furnace, introduce a mixture of argon and hydrogen as a protective gas, heat to 1200-1400℃, hold for 1-4 hours, then cool to 800℃, then cool to room temperature, grind and sieve to obtain boronized nickel-chromium titanate-coated calcium aluminate.
[0015] Preferably, in S1, the mass-to-volume ratio of chromium nitrate, nickel nitrate, boric acid, and anhydrous ethanol is (9.7-10.5)g:(2.4-3.4)g:(5.6-6.8)g:100mL.
[0016] Preferably, in step S1, the dispersant is PEG, specifically at least one of PEG-400, PEG-600, PEG-1000, PEG-1500, and PEG-2000, and the amount of dispersant added is 0.5%-2.5% of the volume of anhydrous ethanol.
[0017] Preferably, in step S2, the concentration of the hydrochloric acid solution is 0.1-0.5 mol / L, and the mass-to-volume ratio of calcium aluminate titanate powder to hydrochloric acid solution is 1 g:(10-20) mL.
[0018] Preferably, in step S3, the mass-to-volume ratio of the pretreated calcium titanate powder to the precursor solution is 10 g:(20-30) mL.
[0019] Preferably, in step S4, the heating rate is 10-30℃ / min, and the cooling rate to 800℃ is 2-5℃ / min.
[0020] Secondly, the present invention provides a method for preparing a rapid repair material for the taphole and lining of an intermediate frequency furnace, comprising the following steps: Step 1: Put the tabular corundum, fused magnesia and silicon carbide into the mixer and mix for 5-10 minutes at a speed of 40-50 rpm. Step 2: Add alumina micro powder, nano-zirconia and reinforcing agent, and continuously spray silica sol while stirring. Continue stirring for 10-20 minutes after spraying. Step 3: Extrude the above mixture using a vacuum extruder to form strips with a diameter of 20-100mm. After cutting, package the strips in aluminum-plastic bags to complete the preparation.
[0021] The beneficial effects of this invention are as follows: 1. This invention provides a rapid repair material for the taphole and lining of a medium-frequency furnace. Plate-shaped corundum is mainly used as the overall skeleton; fused magnesia and alumina micro powder are combined to form high-melting-point magnesium aluminum spinel; nano-zirconia can fill pores and has excellent toughness; silicon carbide has the advantages of high hardness, high thermal conductivity and high melting point; the reinforcing agent is calcium aluminate titanate coated with chromium nickel boride. Although the amount added is small, it can significantly improve the high-temperature strength, toughness and thermal shock resistance of the repair material, especially the long-term corrosion resistance.
[0022] 2. The rapid repair material of the present invention relies on alumina micro powder to form sufficient strength under medium and low temperature conditions, and relies on reinforcing agents to rapidly form a high-strength and dense sintered layer under high temperature conditions.
[0023] 3. The reinforcing agent in the composition uses calcium aluminate titanate as the core layer to provide thermal expansion buffering, reduce the thermal mismatch stress between the overall particles and the matrix, and enhance thermal shock resistance and cladding stability; and chromium nickel boride as the outer cladding layer, providing excellent resistance to chemical erosion and penetration by molten slag. Therefore, the reinforcing agent can not only effectively buffer the difference in thermal expansion between the repair layer and the old lining, but also has a relatively excellent resistance to erosion and penetration, thus extending the repair life.
[0024] 4. The reinforcing agent coating layer of the present invention uses a unique ratio of high chromium and low nickel, which has a more comprehensive performance compared with chromium boride or nickel boride alone. It is significantly better in terms of strength, toughness and interfacial bonding with the matrix. Detailed Implementation
[0025] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.
[0026] The present invention will be further described below with reference to the following embodiments. Example 1
[0027] A quick-repair material for the taphole and lining of an intermediate frequency furnace, comprising, by weight parts: 60 parts tabular corundum, 15 parts fused magnesia, 12 parts alumina micro powder, 5 parts nano zirconium oxide, 5-12 parts silicon carbide, 10-15 parts silica sol, and 2-5 parts reinforcing agent.
[0028] The particle size distribution of the tabular alumina includes: 30% by weight of particles with a particle size of 1-3 mm, 40% by weight of particles with a particle size of 0.5-1 mm, and 30% by weight of particles with a particle size of less than 0.5 mm; the composition of the tabular alumina includes Al2O3≥99%, Na2O≤0.4%, and SiO2≤0.15%.
[0029] The composition of the fused magnesia includes: MgO≥97%, SiO2≤1.2%, CaO≤1.5%, and the particle size of the fused magnesia is 0.088-0.5mm.
[0030] The alumina micro powder has a purity of over 99.5% and a particle size of 0.8-1.2 μm; the nano-zirconia has a purity of over 99% and a particle size of 20-50 nm.
[0031] The silicon carbide has a particle size distribution of 60% by weight with a particle size of 0.5-1 mm and 40% by weight with a particle size of less than 0.5 mm.
[0032] The silica sol contains SiO2 at a mass ratio of 35% ± 1%.
[0033] The reinforcing agent is boronized nickel-chromium titanate coated calcium aluminate, and the preparation method includes: S1. Prepare the precursor solution: Weigh 10.2g of chromium nitrate, 2.9g of nickel nitrate and 6.2g of boric acid and add them to 100mL of anhydrous ethanol. Add 2 drops of nitric acid, then add 1.5% by volume of dispersant PEG-1000 in anhydrous ethanol. Stir thoroughly to obtain the precursor solution. S2. Pretreated calcium titanate powder: Weigh 1g of calcium aluminate titanium dioxide powder and sonicate it in 15mL of 0.2mol / L hydrochloric acid solution for 15min. Then wash it with water and dry it to obtain pretreated calcium aluminate titanium dioxide powder. S3. Coating treatment: 10g of pretreated calcium titanate powder (Al2O3 content 76-78wt%, CaO content 10-12wt%, TiO2 content 10-14wt%) was immersed in 25mL of precursor solution, ultrasonically dispersed for 30min, heated to 75℃, kept at the temperature and continuously stirred to evaporate more than 90% of the solvent, and placed in a drying oven at 250℃ for 2h to obtain precursor-coated powder; S4. Sintering treatment: The precursor-coated powder was placed in a tube furnace, and a mixture of argon and hydrogen (argon to hydrogen volume ratio of 95:5) was introduced as a protective gas. The temperature was increased to 1300℃ at a rate of 20℃ / min and held for 3 hours. Then, it was cooled to 800℃ at a rate of 3℃ / min and then cooled to room temperature in the furnace. After grinding and sieving, boronized nickel-chromium titanate coated calcium aluminate with a particle size of 1.5±0.2μm was obtained.
[0034] The preparation method of the above-mentioned rapid repair material for the taphole and lining of the medium-frequency furnace includes the following steps: Step 1: Put the tabular corundum, fused magnesia and silicon carbide into the mixer and mix for 6 minutes at a speed of 45 rpm. Step 2: Add alumina micro powder, nano-zirconia and reinforcing agent, and continuously spray silica sol while stirring. Continue stirring for 15 minutes after spraying. Step 3: The above mixture is extruded using a vacuum extruder to form strips with a diameter of 50mm. After cutting, the strips are packaged in aluminum-plastic bags to complete the preparation. Example 2
[0035] A quick-repair material for the taphole and lining of an intermediate frequency furnace, comprising, by weight parts: 50 parts tabular corundum, 10 parts fused magnesia, 8 parts alumina micro powder, 3 parts nano zirconium oxide, 5 parts silicon carbide, 10 parts silica sol, and 2 parts reinforcing agent.
[0036] The tabular corundum has the following particle size distribution: 20% by weight of particles with a diameter of 1-3 mm, 30% by weight of particles with a diameter of 0.5-1 mm, and 50% by weight of particles with a diameter less than 0.5 mm. The tabular corundum composition includes Al₂O₃ ≥ 99%, Na₂O ≤ 0.4%, and SiO₂ ≤ 0.15%. The fused magnesia composition includes MgO ≥ 97%, SiO₂ ≤ 1.2%, CaO ≤ 1.5%, and the fused magnesia particle size is 0.088-0.5 mm. The alumina micro powder has a purity higher than 99.5% and a particle size of 0.8-1.2 μm; the nano-zirconia has a purity higher than 99% and a particle size of 20-50 nm; the silicon carbide has a particle size distribution of 50% by weight of particles with a particle size of 0.5-1 mm and 50% by weight of particles with a particle size of less than 0.5 mm; the silica sol has a SiO2 mass percentage of 35% ± 1%; the reinforcing agent is calcium aluminate titanate coated with chromium nickel boride with a particle size of 1 ± 0.2 μm.
[0037] The method for preparing the boronized nickel-chromium titanium aluminate coated calcium includes: S1. Prepare the precursor solution: Weigh 9.7g of chromium nitrate, 2.4g of nickel nitrate and 5.6g of boric acid and add them to 100mL of anhydrous ethanol. Add 2 drops of nitric acid and then add dispersant PEG-1000. The amount added is 0.5% of the volume of anhydrous ethanol. After stirring thoroughly, the precursor solution is obtained. S2. Pretreated calcium titanate powder: Weigh 1g of calcium aluminate titanate powder and sonicate it in 10mL of 0.1mol / L hydrochloric acid solution for 10min. Then wash it with water and dry it to obtain pretreated calcium aluminate titanate powder. S3. Coating treatment: 10g of pretreated calcium titanate powder was immersed in 20mL of precursor solution, ultrasonically dispersed for 20min, heated to 70℃, kept at the temperature and continuously stirred to evaporate more than 90% of the solvent, and then placed in a drying oven at 200℃ for 1h to obtain precursor-coated powder. S4. Sintering treatment: The precursor-coated powder was placed in a tube furnace, and a mixture of argon and hydrogen (argon to hydrogen volume ratio of 95:5) was introduced as a protective gas. The temperature was raised to 1200℃ at a rate of 10℃ / min and held for 1 hour. Then, it was cooled to 800℃ at a rate of 2℃ / min and then cooled to room temperature in the furnace. After grinding and sieving, chromium nickel boride-coated calcium aluminate titanate was obtained.
[0038] The preparation method of the above-mentioned rapid repair material for the taphole and lining of the medium-frequency furnace includes the following steps: Step 1: Put the tabular corundum, fused magnesia and silicon carbide into the mixer and mix for 5 minutes at 40 rpm. Step 2: Add alumina micro powder, nano-zirconia and reinforcing agent, and continuously spray silica sol while stirring. Continue stirring for 10 minutes after spraying. Step 3: The above mixture is extruded using a vacuum extruder to form strips with a diameter of 50mm. After cutting, the strips are packaged in aluminum-plastic bags to complete the preparation. Example 3
[0039] A quick-repair material for the taphole and lining of an intermediate frequency furnace, comprising, by weight parts: 70 parts tabular corundum, 20 parts fused magnesia, 15 parts alumina micro powder, 8 parts nano zirconium oxide, 12 parts silicon carbide, 15 parts silica sol, and 5 parts reinforcing agent.
[0040] The tabular corundum has the following particle size distribution: 40% by weight of particles with a diameter of 1-3 mm, 40% by weight of particles with a diameter of 0.5-1 mm, and 20% by weight of particles with a diameter less than 0.5 mm. The tabular corundum composition includes Al₂O₃ ≥ 99%, Na₂O ≤ 0.4%, and SiO₂ ≤ 0.15%. The fused magnesia composition includes MgO ≥ 97%, SiO₂ ≤ 1.2%, CaO ≤ 1.5%, and the fused magnesia particle size is 0.088-0.5 mm. The alumina micro powder has a purity higher than 99.5% and a particle size of 0.8-1.2 μm; the nano-zirconia has a purity higher than 99% and a particle size of 20-50 nm; the silicon carbide has a particle size distribution of 70% by weight of particles with a particle size of 0.5-1 mm and 30% by weight of particles with a particle size of less than 0.5 mm; the silica sol has a SiO2 mass percentage of 35% ± 1%; the reinforcing agent is calcium aluminate titanate coated with chromium nickel boride and has a particle size of 0.5-2 μm.
[0041] The method for preparing the boronized nickel-chromium titanium aluminate coated calcium includes: S1. Prepare the precursor solution: Weigh 10.5g of chromium nitrate, 3.4g of nickel nitrate and 6.8g of boric acid and add them to 100mL of anhydrous ethanol. Add 3 drops of nitric acid and then add dispersant PEG-1000. The amount added is 2.5% of the volume of anhydrous ethanol. After stirring thoroughly, the precursor solution is obtained. S2. Pretreated calcium titanate powder: Weigh 1g of calcium aluminate titanium dioxide powder and sonicate it in 20mL of 0.5mol / L hydrochloric acid solution for 20min. Then wash it with water and dry it to obtain pretreated calcium aluminate titanium dioxide powder. S3. Coating treatment: 10g of pretreated calcium titanate powder was immersed in 30mL of precursor solution, ultrasonically dispersed for 40min, heated to 80℃, kept at the temperature and continuously stirred to evaporate more than 90% of the solvent, and then placed in a drying oven at 300℃ for 3h to obtain precursor-coated powder. S4. Sintering treatment: The precursor-coated powder was placed in a tube furnace, and a mixture of argon and hydrogen (argon to hydrogen volume ratio of 95:5) was introduced as a protective gas. The temperature was raised to 1400℃ at a rate of 30℃ / min and held for 4 hours. Then, it was cooled to 800℃ at a rate of 5℃ / min and then cooled to room temperature in the furnace. After grinding and sieving, chromium nickel boride-coated calcium aluminate titanate was obtained.
[0042] The preparation method of the above-mentioned rapid repair material for the taphole and lining of the medium-frequency furnace includes the following steps: Step 1: Put the tabular corundum, fused magnesia and silicon carbide into the mixer and mix for 10 minutes at 50 rpm. Step 2: Add alumina micro powder, nano-zirconia and reinforcing agent, and continuously spray silica sol while stirring. Continue stirring for 20 minutes after spraying. Step 3: The above mixture is extruded using a vacuum extruder to form strips with a diameter of 50mm. After cutting, the strips are packaged in aluminum-plastic bags to complete the preparation.
[0043] Comparative Example 1 A rapid repair material for the tap hole and furnace lining of a medium-frequency furnace is different from that in Example 1 only in that the reinforcing agent in the composition is replaced with an equal weight of calcium aluminate titanium powder.
[0044] Comparative Example 2 A rapid repair material for the tap hole and furnace lining of a medium-frequency furnace differs from Example 1 only in that the reinforcing agent in the composition is replaced by a mixture of chromium boride (CrB2) and calcium titanate powder, with a mass ratio of chromium boride to calcium titanate powder of 1:2.
[0045] Comparative Example 3 A rapid repair material for the tap hole and lining of a medium-frequency furnace differs from Example 1 only in that the reinforcing agent in the composition is replaced by a mixture of nickel boride (Ni2B) and calcium aluminate titanium dioxide powder, with a mass ratio of nickel boride to calcium aluminate titanium dioxide powder of 1:2.
[0046] To more clearly illustrate the content of the present invention, the performance of the rapid repair materials prepared in Example 1 and Comparative Examples 1-3 of the present invention was tested.
[0047] The specific usage method of the quick repair material is as follows: The furnace lining of the medium-frequency furnace to be repaired is sandblasted to Sa2.5 grade (roughness Ra≥50μm), preheated to 200℃ for 1 hour, and then the prepared rapid repair material is unsealed and applied to the area to be repaired, with a coating thickness of 20 mm. After compaction, it is baked in stages: from room temperature to 250℃, heating rate 50℃ / h, holding for 2 hours; from 250℃ to 1000℃, heating rate 100℃ / h, holding for 3 hours; from 1000℃ to 1500℃, heating rate 150℃ / h, holding for 2 hours, then cooled to 600℃ at a cooling rate of 80℃ / h, and then air-cooled to room temperature to complete the repair.
[0048] The basic properties and performance of the quick-repair material after repair were tested, including: (1) Test the basic properties of the quick-repair material, such as hardening time, strength, and toughness: The testing methods include: For heat hardening time testing, refer to YB / T 4117-2003 "Test Method for Crack Resistance of Dense Refractory Castables", with parameters of 1400℃ and 0.3MPa; for flexural strength (room temperature / high temperature), refer to GB / T 3001-2017 "Test Method for Flexural Strength of Refractory Materials at Room Temperature", with a sample size of 25×25×125mm; for bond strength testing, refer to GB / T22459.4-2008, the interfacial strength test between rapid repair material and magnesia-alumina spinel brick after heat treatment at 1400℃; for fracture toughness testing, refer to ASTM C1421-2018 "Standard Test Method for Fracture Toughness of Ceramics", with parameters of three-point bending method and a notch depth of 2.5mm.
[0049] The test results are shown in Table 1:
[0050] (2) The performance of the rapid repair material, including its thermal shock resistance, slag erosion resistance index, and number of cycles, was tested: The testing methods include: Thermal shock resistance testing refers to GB / T 30873-2014 "Test Method for Thermal Shock Resistance of Refractory Materials", involving water cooling from 1100℃ to 25℃, cycling until the flexural strength decreases by 50%; Erosion resistance index: Slag erosion resistance index testing refers to GB / T 8931-2007 "Test Method for Slag Resistance of Refractory Materials", 1600℃×4h, alkaline slag (CaO / SiO2=2) / acidic slag (SiO2=55%); Cycle life testing is the number of times the medium-frequency furnace (≤1600℃) is used from the completion of repair to the failure of the repair layer.
[0051] The test results are shown in Table 2:
[0052] The test results in Tables 1 and 2 show that the rapid repair material prepared in Example 1 exhibits high strength at both low and high temperatures, especially with a significant increase in strength at high temperatures, indicating the formation of a high-strength and dense sintered layer at high temperatures. Furthermore, it possesses excellent toughness, bonding strength, and thermal shock resistance, particularly in long-term erosion resistance, resulting in a significantly extended service life. In Comparative Example 1, although calcium aluminate has the advantage of low thermal expansion, its hardness and chemical inertness are far inferior to those of Example 1, resulting in insufficient protection. In Comparative Examples 2 and 3, although chromium boride or nickel boride was introduced, its performance was not as enhanced as that of chromium-nickel boride-coated calcium aluminate in Example 1.
[0053] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A rapid repair material for the taphole and lining of a medium-frequency furnace, characterized in that, Calculated by weight, including: 50-70 parts tabular corundum, 10-20 parts fused magnesia, 8-15 parts alumina micro powder, 3-8 parts nano zirconium oxide, 5-12 parts silicon carbide, 10-15 parts silica sol and 2-5 parts reinforcing agent; The reinforcing agent is calcium aluminate titanate coated with chromium nickel boride.
2. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 1, characterized in that, The particle size distribution of the tabular alumina includes: 20%-40% by weight of particles with a diameter of 1-3 mm, 30%-50% by weight of particles with a diameter of 0.5-1 mm, and 20%-40% by weight of particles with a diameter less than 0.5 mm; the composition of the tabular alumina includes Al2O3≥99%, Na2O≤0.4%, and SiO2≤0.15%.
3. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 1, characterized in that, The composition of the fused magnesia includes: MgO≥97%, SiO2≤1.2%, CaO≤1.5%, and the particle size of the fused magnesia is 0.088-0.5mm.
4. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 1, characterized in that, The alumina micro powder has a purity higher than 99.5% and a particle size of 0.8-1.2 μm; the nano-zirconia has a purity higher than 99% and a particle size of 20-50 nm.
5. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 1, characterized in that, The particle size distribution of the silicon carbide includes: 50%-70% by weight of particles with a diameter of 0.5-1 mm and 30%-50% by weight of particles with a diameter less than 0.5 mm; the mass percentage of SiO2 in the silica sol is 20%-55%.
6. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 1, characterized in that, The method for preparing the boronized nickel-chromium titanium aluminate coated calcium includes: S1. Weigh chromium nitrate, nickel nitrate and boric acid and add them to anhydrous ethanol. Add 2-3 drops of nitric acid, then add dispersant and stir thoroughly to obtain the precursor solution. S2. Weigh the calcium aluminate titanium dioxide powder, sonicate it in hydrochloric acid solution for 10-20 minutes, wash it with water and dry it to obtain pretreated calcium aluminate titanium dioxide powder. S3. Immerse the pretreated calcium titanate powder in the precursor solution, ultrasonically disperse for 20-40 minutes, heat to 70-80℃, keep warm and continuously stir to evaporate more than 90% of the solvent, and place in a drying oven at 200-300℃ for 1-3 hours to form the precursor-coated powder. S4. Place the precursor-coated powder in a tube furnace, introduce a mixture of argon and hydrogen as a protective gas, heat to 1200-1400℃, hold for 1-4 hours, then cool to 800℃, then cool to room temperature, grind and sieve to obtain boronized nickel-chromium titanate-coated calcium aluminate.
7. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 6, characterized in that, In S1, the mass-to-volume ratio of chromium nitrate, nickel nitrate, boric acid, and anhydrous ethanol is (9.7-10.5)g:(2.4-3.4)g:(5.6-6.8)g:100mL.
8. The rapid repair material for the taphole and lining of a medium-frequency furnace according to claim 6, characterized in that, In S2, the concentration of hydrochloric acid solution is 0.1-0.5 mol / L, and the mass-to-volume ratio of calcium aluminate titanate powder to hydrochloric acid solution is 1 g:(10-20) mL.
9. A rapid repair material for the taphole and lining of an intermediate frequency furnace according to claim 6, characterized in that, In S3, the mass-to-volume ratio of the pretreated calcium titanate powder to the precursor solution is 10 g:(20-30) mL.
10. A method for preparing the rapid repair material for the taphole and lining of an intermediate frequency furnace as described in claim 1, characterized in that, Includes the following steps: Step 1: Put the tabular corundum, fused magnesia and silicon carbide into the mixer and mix for 5-10 minutes at a speed of 40-50 rpm. Step 2: Add alumina micro powder, nano-zirconia and reinforcing agent, and continuously spray silica sol while stirring. Continue stirring for 10-20 minutes after spraying. Step 3: Extrude the above mixture using a vacuum extruder to form strips with a diameter of 20-100mm. After cutting, package the strips in aluminum-plastic bags to complete the preparation.
Citation Information
Cited By
Preparation method of stemming with high oxidation resistance and high binding property
CN121591495A
Preparation method of high-oxidation-resistance and high-bonding-quality quoin
CN121591495B